Development of a laboratory test for characterization of asphalt-aggregate adhesion - Pais, Jorge C. (2002)
The mechanical properties of bituminous mixtures depend on the adhesion between mastic and aggregate, as well as on the cohesion within the mastic. These properties vary as a function of the composition of the bituminous mixture, of the chemical and physical features of the aggregate and bitumen and of the condition under which the mixing is carried out. It is thus fundamental to develop an adhesion test, which is of easy execution and, at the same time, represents correctly the bituminous mixture and its mechanical behaviour, essentially the aggregate-mastic adhesion. The test described here simulates the behaviour of a small representative specimen of the bituminous material subject to increasing tension or shear force, inducing rupture of the aggregate-mastic bond. The specimens have a prismatic shape and comprise a single large piece of aggregate between two layers of mastic. The efficiency of the aggregate-mastic bond will be evaluated by the necessary force to rupture the specimen and by the form of rupture. The results obtained from this test will not only allow the features which most influence the adhesion of mastic to aggregate to be established, but also reveal the best aggregate-fines-binder combinations as a function of the type of aggregate and bituminous mixture.